PERANCANGAN BED REACTOR ZEOLIT JENIS ALIRAN TURBULEN SEBAGAI ALAT PENYERAP POLUTAN GAS ASAP PADA MOTOR BAKAR BENSIN - KHAIDIR .; AMRU SIREGAR; AMIRSYAM NASUTION (LP2MTBM MAKARIOZ, 2020)
Natural Zeolite Minerals are a group of minerals consisting of oxides Al2O3, SiO3, Fe2O3, CaO, and MgO. These compilersof zeolite are found in sedimentary rocks, especially minerals originating from the alumina and silicate groups. The details ofzeolite that have been activated can absorb toxic gases such as NO, CO, SO2, H2S, and others. Therefore this zeolitepowder can be used as an absorbent material (adsorbent) gas pollutants from the smoke gas automotive engine. Naturalzeolite as an adsorb material requires AIDS, in this case it is called the bed reactor. Power absorption bed reactor againstgas CO, CO2, and HC is measured using smoke tester type SPTC anycar Auto Chek Gas & Smoke version 1.5.1. E-1.Analysis of measurement results expressed in the number of% volumes for gas CO and CO2 gases. As for HC gas in PPMunits. The results of the test show the bed reactor type of turbulent flow has absorbent power (ADSORBSI) of 53% for gasCO, 52% for CO2 gas, and 41% for gas HC, respectively for large grain 40 mesh. Similarly, absorption (ADSORBSI),amounting to 42% for gas CO, 47% for CO2 gas, and 35% gas download HC, respectively for a large 10 mesh grain.Furthermore, 33% for gas CO, 33% for CO2 gas, and 30% gas download HC, respectively for a large 20 mesh grain.